YMDD motif mutations in chronic hepatitis B antiviral treatment naïve patients: a multi-center study - Tan,You-Wen (2012)
OBJECTIVE: This study aimed to determine the natural prevalence of variants of tyrosine-methionine-aspartic acid-aspartic acid (YMDD) motif in patients with chronic hepatitis B (CHB), and to explore its relation with demographic and clinical features, hepatitis B virus (HBV) genotypes, and HBV DNA levels. METHODS: A total of 1,042 antiviral treatment naïve CHB patients (including with lamivudine [LAM]) in the past year were recruited from outpatient and inpatient departments of six centers from December 2008 to June 2010. YMDD variants were analyzed using the HBV drug resistance line probe assay (Inno-Lipa HBV-DR). HBV genotypes were detected with polymerase chain reaction (PCR) microcosmic nucleic acid cross-ELISA, and HBV deoxyribonucleic acid (DNA) was quantitated with real-time PCR. All serum samples underwent tests for HBV, HCV, and HDV with ELISA. RESULTS: YMDD variants were detected in 23.3% (243/1042) of CHB patients. YMDD mutation was accompanied by L180M mutation in 154 (76.9%) patients. Both wild-type HBV and YMDD variant HBV were present in 231 of 243 patients. Interestingly, 12 patients had only YIDD and/or YVDD variants without wild YMDD motif. In addition, 27.2% (98/359) of HbeAg-positive patients had YMDD mutations, which was higher than that in HbeAg-negative patients (21.2%, 145/683). The incidence of YMDD varied among patients with different HBV genotypes, but the difference was not significant. Moreover, the incidence of YMDD in patients with high HBV DNA level was significantly higher than that in those with low HBV DNA level. CONCLUSION: Mutation of YMDD motif was detectable at a high rate in CHB patients in this study. The incidence of YMDD may be correlated with HBeAg and HBV DNA level.